Deep dechlorination of model oil by reactive adsorption on porous oxides. (15th November 2021) - Niu, Hui; Zhao, Dongzhi; Xie, Guoying; Yuan, Yanan; Zhang, Wei; Zhang, Chen; Li, Cuiqing; Cui, Lingyan
Highlights: Removal of 1-chlorooctane reached 99% over Al2 O3 -9.5 at 150 °C. 1-Chlorooctane was converted into 1-octanol and Cl − on porous oxides at 150 °C. The Lewis acid amount on the adsorbent governs its dechlorination performance. Abstract: Al2 O3, TiO2, ZrO2 and SiO2 were used for adsorptive dechlorination of model oil at different temperatures. The results showed that chlorine removal over the four mesoporous oxides sharply increased with increasing the temperature from 20 °C to 150 °C. GC–MS and ion chromatography analysis showed that 1-chlorooctane was converted into 1-octanol and chloride ion at the temperature higher than 120 °C, which were then adsorbed on the adsorbent. Precipitation pH had a significant impact on the dechlorination performance of Al2 O3 . Among various porous oxides, Al2 O3 -9.5 precipitated at pH 9.5 exhibited the highest dechlorination performance, over which the chlorine removal reached 99% after adsorption for 3 h at 150 °C. The characterization results indicated that various porous oxides contained only Lewis acid, and the dechlorination performance of the adsorbent basically increased with the increase of its total Lewis acid amount. The dechlorination efficiency for different organochlorine compounds followed the order: straight chain alkyl chlorides > chlorinated cycloalkanes > aromatic hydrocarbons. Al2 O3 -9.5 showed good regenerability, and the dechlorination performance of Al2 O3 -9.5 had only a slight decrease after six consecutive dechlorination-regeneration cycles, due to slight loss of its Lewis acid amount and surface area.